TOPD Phenotype versus COPD: Pulmonary Function Spectrum Beyond the Limits of Spirometry - Bishal Debbarma; Anand Srivastava; Sapna Dixit; Rajiv Garg; S.K Verma; RAS Kushwaha; Santosh Kumar; Ajay Kumar Verma; Darshan Kumar Bajaj; Ankit Kumar; Jyoti Bajpai; Surya Kant (The Journal of Association of Chest Physicians)
Aims: To compare the lung functions of TOPD phenotype patients and COPD patients other than TOPD phenotype. Settings and design: Retro-prospective cohort study. Introduction: Globally, tuberculosis (TB) has emerged as a risk factor for the development of chronic obstructive pulmonary disease (COPD) and is one of the leading causes of mortality and morbidity. This entity has been titled as TOPD phenotype (tuberculosis-associated obstructive pulmonary disease), and it has been mentioned in various literatures in the past by various authors. However, it is still a matter of debate whether pattern of chronic airflow obstruction in COPD and TOPD phenotype is different or same. Methodology: We enrolled a total of 100 patients, in that 50 of whom had obstructive airway symptoms with a history of (treated) pulmonary tuberculosis (with a microbiological or radiological evidence in the past) and 50 of whom were diagnosed with COPD without any history of tuberculosis. Both groups underwent spirometry and impulse oscillometry (IOS) tests. Results were recorded and compared. Results: The mean age of patients with TOPD was 49.51 ± 5.15, while COPD was 48.54 ± 5.94. The chance of exacerbation was higher in the TOPD group (94.0%) owing to poor lung function. The majority of TOPD patients were in GOLD II stage, while COPD patients were in GOLD I stage. Spirometry and IOS of TOPD patients revealed a significant difference as compared to COPD patients. Conclusion: We found that overall lung function was poorer in the TOPD group as compared to the COPD group.